TOTAL KANDUNGAN FLAVONOID DAN PEMBUATAN FORMULASI SALEP EKSTRAK ETANOL KULIT UBI JALAR UNGU (Ipomea Batatas L.) ASAL KOTA PALU SULAWESI TENGAH TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Viani Anggi; Dewi Sufiani (Jurnal Ilmiah Manuntung, 2019)
Purple sweet potato rind has content of flavonoid and inhibitory activity against Staphylococcus aureus bacteria. This study aims to determine the content of flavonoid and difference between variations in the concentration of purple sweet potato rind ointment as inhibitory capacity to produce the physical quality of ointment that is in accordance with Indonesian Pharmacopoeia requirements and to know the difference in activity of inhibition of purple sweet potato rind ointment between variations in concentration on Staphylococcus aureus. The research method used has total flavonoid equivalent quercetin by spectrophotometry uv-vis and to inhibitory activity was used the paper disk method, namely by applying Staphylococcus aureus bacteria culture using sterile cotton sticks and then placed paper discs which had been soaked for 15 minutes with purple sweet potato rind extract ointment. Purple sweet potato rind extract was obtained by maceration using 96% ethanol solvent until the ethanol extract of purple sweet potato rind was obtained. It was then formulated into ointment dosage forms with variations in concentrations of 20%, 25%, 30%. The results showed has total flavonoid equivalent quercetin of purple sweet potato rind is 8,36% and the variation of the concentration of purple sweet potato rind ointment influential in producing the physical quality of the ointment, the ointment the concentration of 30% produced a distinctive aroma and brighter colors from concentrations of 20% and 25%. The inhibitory activity of purple sweet potato rind extract ointment showed a significant value of < 0,05 (p=0,000) at a concentration of 30% having a strong inhibitory activity against the Staphylococcus aureus bacteria.